Horizonte subjetivo de nuestra época (2012)
ABSTRACT: The expression “Let whoever cannot meet at its horizon the subjectivity of his time give it up then”, said by Lacan in 1953 in his The Function and Field of Speech and Language in Psychoanalysis, is analyzed in order to articulate it to the prescription made by Lacan to the analysis concerning the analyst´s desire, the analyst´s place, the analyst´s speech and the analyst´s formation. This warning shows how the psychoanalytic practice is not as related to deontological codes as it is to the asceticism demanded by the work with the significant.